Cleavage Specificity of the UL48 Deubiquitinating Protease Activity of Human Cytomegalovirus and the Growth of an Active-Site Mutant Virus in Cultured Cells - Eui Tae Kim; Se Eun Oh; Yun-Ok Lee; Wade Gibson; Jin-Hyun Ahn (2009)
The human cytomegalovirus (HCMV) open reading frame UL48 encodes a 253-kDa tegument protein that is closely associated with the capsid and was recently shown to have ubiquitin-specific protease activity (J. Wang, A. N. Loveland, L. M. Kattenhorn, H. L. Ploegh, and W. Gibson, J. Virol. 80:6003-6012, 2006). Here, we examined the cleavage specificity of this deubiquitinase (DUB) and replication characteristics of an active-site mutant virus. The purified catalytic domain of the UL48 DUB (1 to 359 amino acids), corresponding to the herpes simplex virus UL36(USP) DUB (L. M. Kattenhorn, G. A. Korbel, B. M. Kessler, E. Spooner, and H. L. Ploegh, Mol. Cell 19:547-557, 2005), efficiently released ubiquitin but not ubiquitin-like modifications from a hemagglutinin peptide substrate. Mutating the active-site residues Cys24 or His162 (C24S and H162A, respectively) abolished this activity. The HCMV UL48 and HSV UL36(USP) DUBs cleaved both Lys48- and Lys63-linked ubiquitin dimers and oligomers, showing more activity toward Lys63 linkages. The DUB activity of the full-length UL48 protein immunoprecipitated from virus-infected cells also showed a better cleavage of Lys63-linked ubiquitinated substrates. An HCMV (Towne) mutant virus in which the UL48 DUB activity was destroyed [UL48(C24S)] produced 10-fold less progeny virus and reduced amounts of viral proteins compared to wild-type virus at a low multiplicity of infection. The mutant virus also produced perceptibly less overall deubiquitination than the wild-type virus. Our findings demonstrate that the HCMV UL48 DUB contains both a ubiquitin-specific carboxy-terminal hydrolase activity and an isopeptidase activity that favors ubiquitin Lys63 linkages and that these activities can influence virus replication in cultured cells.